Cost-effectiveness of the HiBalance training program for elderly with Parkinson's disease: analysis of data from a randomized controlled trial. (February 2019) - Joseph, Conran; Brodin, Nina; Leavy, Breiffni; Hagströmer, Maria; Löfgren, Niklas; Franzén, Erika
Objective: To determine the cost-effectiveness of the HiBalance training program for managing Parkinson's disease (PD)-related balance and gait disorders. Design: Cost comparison design following the randomized controlled trial comparing a novel balance training intervention with care as usual. Subjects: A total of 100 participants with mild–moderate PD were randomized to either the intervention ( n  = 51) or the control group ( n  = 49). Intervention: A 10-week (three times per week), group-based, progressive balance training program, led by two physical therapists. Main outcomes: All program costs were collected for both groups. Cost-utility was evaluated using quality-adjusted life years (QALYs) and cost-effectiveness measures were the Mini Balance Evaluation Systems Test (Mini-BESTest; assessing balance performance) and gait velocity. Incremental cost-effectiveness ratios were calculated and a probabilistic sensitivity analysis was conducted. Results: The between-group difference in QALYs was 0.043 (95% confidence interval (CI): 0.011–0.075), favoring the intervention group. Between-group differences in balance performance and gait velocity were 2.16 points (95% CI: 1.19–3.13) and 8.2 cm/second (95% CI: 2.9–13.6), respectively, favoring the intervention group. The mean cost per participant in the intervention group was 16, 222 SEK (€1649) compared to 2696 SEK (€274) for controls. The estimated incremental cost-effectiveness ratios were 314, 558 SEK (€31, 969) for an additional QALY, 6262 SEK (€631) for one point improvement in balance performance, and 1650 SEK (€166) for 1 cm/second increase in gait velocity. Sensitivity analyses indicated a high probability (85%) of program success. Conclusion: In terms of QALYs, the HiBalance program demonstrated a high probability of cost-effectiveness in the short-term perspective when considering the willingness-to-pay thresholds used in Europe.